2008
DOI: 10.1093/hmg/ddn124
|View full text |Cite
|
Sign up to set email alerts
|

A nonsense mutation in the LIMP-2 gene associated with progressive myoclonic epilepsy and nephrotic syndrome

Abstract: The main clinical features of two siblings from a consanguineous marriage were progressive myoclonic epilepsy without intellectual impairment and a nephrotic syndrome with a strong accumulation of C1q in capillary loops and mesangium of kidney. The biochemical analysis of one of the patients revealed a normal beta-glucocerebrosidase activity in leukocytes, but a severe enzymatic deficiency in cultured skin fibroblasts. This deficiency suggested a defect in the intracellular sorting pathway of this enzyme. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 29 publications
5
80
0
4
Order By: Relevance
“…Flow cytometric analyses revealed that the two representative clones that highly expressed GBA1 had lower levels of cell surface SCARB2 than their corresponding control (Figs 3 and S1), suggesting that the cell surface levels of SCARB2 were reduced by GBA1 expression. Given the transporter activity of SCARB2 [13,14], it seems likely that GBA1 overexpression may increase SCARB2 trafficking through the ER-Golgilysosome pathway, resulting in a reduction in SCARB2 targeting to the cell surface.…”
Section: Analysis Of the Anti-ev71 Mechanism Of Gba1mentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometric analyses revealed that the two representative clones that highly expressed GBA1 had lower levels of cell surface SCARB2 than their corresponding control (Figs 3 and S1), suggesting that the cell surface levels of SCARB2 were reduced by GBA1 expression. Given the transporter activity of SCARB2 [13,14], it seems likely that GBA1 overexpression may increase SCARB2 trafficking through the ER-Golgilysosome pathway, resulting in a reduction in SCARB2 targeting to the cell surface.…”
Section: Analysis Of the Anti-ev71 Mechanism Of Gba1mentioning
confidence: 99%
“…A mutation in SCARB2 was found to cause downregulation of GBA1 expression in epithelial cells [14], suggesting that SCARB2 may function as a molecular chaperone of GBA1. Factors that enhance EV71 infection have also been reported, including annexin II and heparin sulfate [14,15] [8,16,17]. However, intrinsic negative regulators of EV71 replication have not been documented.…”
Section: Introductionmentioning
confidence: 99%
“…It was initially described in French-Canadians but it has been reported in patients with various ethnic origins (Andermann et al, 1986;Badhwar et al, 2004). It is caused by the deficiency of the lysosomal integral membrane protein type 2 (LIMP-2) (Berkovic et al, 2008, Balreira et al, 2008, an ubiquitously expressed transmembrane protein (Fujita et al , 1992) mainly found in the lysosomes and late endosomes (Fukuda, 1991), that mediates the mannose 6-phosphate-independent targeting of GBA to the lysosomes (Reczek et al, 2007). The deficient activity of LIMP-2 leads to the mistarget of the GBA protein, which can not reach the lysosome.…”
Section: Action Myoclonus-renal Failure Syndrome (Amrf)mentioning
confidence: 99%
“…The deficient activity of LIMP-2 leads to the mistarget of the GBA protein, which can not reach the lysosome. In fact, this condition is characterized by pathological levels of GBA activity in fibroblasts, normal or slightly reduced levels in leukocytes, but increased levels in plasma (Balreira et al, 2008;Dardis et al, 2009). …”
Section: Action Myoclonus-renal Failure Syndrome (Amrf)mentioning
confidence: 99%
See 1 more Smart Citation